PARADIGMA PENDIDIKAN TERPADU; Strategi Penguatan Pendidikan Agama di Sekolah - Siswanto Siswanto (Karsa: Journal of Social and Islamic Culture)
AbstractThe dichotomy of religious science and general science has become serious problem that haunts the education system among Muslims.  It implies the development of religious education that seperates the life and after-life matters. One of the sollutions is by placing the unification of the epistimology and theory of educational system into a system. This is to find out the synthesis of educational system by stressing the balance aspect and must be developed thriugh the use of human natura pillars that is covered by religious teaching. The focus of the target would be on integrative and multi-dimensional aspects of students---cognitice, psychomotoric, and affective. It means that an integrative education is not only a matter of one way educational process but also the multi-dimensional education process. It goes around physical and psychological processes, intellectual, behavior, and social.  On the context of religious education systematic and organism models are built upon the components of cooperation, living togetehr, integratively. These models point certain objectives---the realization of religious life, and inspired with religious teaching and values. Kata-kata kunciPendidikan Terpadu, Pendidikan Agama, Sekolah